Pengembangan Media Pembelajaran Wordwall dalam Teks Cerpen Siswa Kelas XI MAS Proyek Univa Medan - Rosmaini, Rosmaini; Ali, Ali; Safina, Nila (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aims to describe the development process and feasibility of Wordwall learning media in short story texts for XI grade students at MAS Project Univa Medan. The population comprised students from XI MIPA 1, XI MIPA 2, XI IIS, and XI IIA, totaling 100 students, with a sample of 31 students from class XI IIS. Data were collected through questionnaires, observation, interviews, documentation, and questionnaires to explore learning website-based short story material on Wordwall media. Following the Research and Development (R&D) model by Borg and Gall, the study progressed through stages including information gathering, product development, validation test, product revision, and product trial. Results show that Wordwall learning media for short story texts in XI MAS Project Univa Medan are highly feasible. Material experts rated it "Decent" (80%) and "Very Decent" (86%), while media experts rated it "Very Decent" (94%) and (93%), and teachers rated it "Very Decent" (91%). Field implementation tests with 31 students yielded a "Very Feasible" rating (90%). Evaluation tests indicated Wordwall's effectiveness in short story texts, with a "Very Effective" rating (90%).